2021
DOI: 10.1136/bmjresp-2020-000824
|View full text |Cite
|
Sign up to set email alerts
|

Typical within and between person variability in non-invasive ventilator derived variables among clinically stable, long-term users

Abstract: BackgroundDespite increasing capacity to remotely monitor non-invasive ventilation (NIV), how remote data varies from day to day and person to person is poorly described.MethodsSingle-centre, 2-month, prospective study of clinically stable adults on long-term NIV which aimed to document NIV-device variability. Participants were switched to a ventilator with tele-monitoring capabilities. Ventilation settings and masking were not altered. Raw, extensible markup language data files were provided directly from Phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Normative ranges may vary more between patients rather than within patients, as demonstrated by Jeganathan and colleagues ( 10 ). Thus, intervention thresholds should be tailored to each patient’s unique physiology.…”
Section: Data Reliability and Accuracymentioning
confidence: 95%
“…Normative ranges may vary more between patients rather than within patients, as demonstrated by Jeganathan and colleagues ( 10 ). Thus, intervention thresholds should be tailored to each patient’s unique physiology.…”
Section: Data Reliability and Accuracymentioning
confidence: 95%
“…Was die Vorhersage einer klinischen Verschlechterung durch telemedizinisch übertragene Daten angeht, gibt es eine Vielzahl von Vorschlägen bezüglich der dafür relevanten Parameter [67,68,73]. Dabei scheint die Betrachtung individueller Trends sinnvoller zu sein, als generelle Schwellenwerte zu definieren [74].…”
Section: Telematik In Der Beatmungsmedizinunclassified
“…Two studies confirmed that the ventilatory rate is higher and increases in the days preceding hospitalization for COPD exacerbation [ 50 , 51 ]. However, finding a threshold for an alert is challenging because the signal is in the same range as the normal variations of respiratory rate in stable patients [ 52 ].…”
Section: Telemonitoringmentioning
confidence: 99%